2014
DOI: 10.2174/1874192401408010113
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Valve Regurgitation Following Temporary or Permanent Endocardial Lead Insertion, and the Impact of Cardiac Resynchronization Therapy

Abstract: Background: While some studies indicate that permanent pacemaker implantation is associated with development of tricuspid regurgitation (TR), other studies indicate no association.Little is known about the impact of temporary lead insertion during ablation procedures, or whether therapy (CRT) prevents TR post-device implantation.Hypothesis: We hypothesized that permanent, but nottemporary endocardial leads, are associated with development of TR, and that CRT would prevent (physiologic) TR.Methods: We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 27 publications
0
4
1
1
Order By: Relevance
“…Right Ventricular Dysfunction Many patients with permanent pacemaker have right side heart failure symptoms that leads to development of tricuspid regurgitation. 16,17 In contrast, RV dysfunction showed no significant correlation with presence of meaningful tricuspid regurgitation in this study. This suggests that chronic RV pacing could lead to right heart failure without clinically significant TR and associated RV dysfunction.…”
Section: Discussioncontrasting
confidence: 72%
“…Right Ventricular Dysfunction Many patients with permanent pacemaker have right side heart failure symptoms that leads to development of tricuspid regurgitation. 16,17 In contrast, RV dysfunction showed no significant correlation with presence of meaningful tricuspid regurgitation in this study. This suggests that chronic RV pacing could lead to right heart failure without clinically significant TR and associated RV dysfunction.…”
Section: Discussioncontrasting
confidence: 72%
“…The authors suggest that chronic RV pacing might thus be responsible for increased TR through left heart deterioration and pulmonary venous congestion rather than direct alterations of the RV or TV . Cardiac resynchronization therapy (CRT) may, therefore, offer a solution to treat or avoid this phenomenon, and a small retrospective study demonstrated a lack of increased TR in a cohort of patients receiving CRT compared to worsened TR in patients receiving non‐CRT PPMs or ICDs . Selection criteria for preventative or secondary CRT implantation to avoid this phenomenon are unclear …”
Section: Mechanisms Of Tv Dysfunctionmentioning
confidence: 99%
“…[8][9][10] Even though pacing the left ventricle via a coronary sinus lead may be an option for the chronic management of patients with AV valve regurgitation secondary to right ventricular pacing, this is not a viable intraoperative management strategy. 6,11 Other than reverting to the patient's underlying rhythm, which resolved the issue in the previous case, intraoperative management options include reliance on the native conduction pathway via an atrial pacing mode, instituting atrial and ventricular pacing to optimize the AV interval, or changing the location of the epicardial lead. 12 If the previously described alterations to electrical activation do not correct new functional tricuspid regurgitation fully, an unnecessary procedure may be avoided by recognizing epicardial right ventricular pacing as a possible cause of new tricuspid regurgitation.…”
Section: Ventricular Pacingàinduced Tricuspid Regurgitation After Carmentioning
confidence: 99%